If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 99 + -4s + -6s = -1 Combine like terms: -4s + -6s = -10s 99 + -10s = -1 Solving 99 + -10s = -1 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-99' to each side of the equation. 99 + -99 + -10s = -1 + -99 Combine like terms: 99 + -99 = 0 0 + -10s = -1 + -99 -10s = -1 + -99 Combine like terms: -1 + -99 = -100 -10s = -100 Divide each side by '-10'. s = 10 Simplifying s = 10
| 32-6= | | -2x-12=6-3x | | 4nm+2sm-10n-5s=0 | | 4x^2-3x+17=0 | | 16r-8r=-1 | | -6x-68=103+3x | | 12x+3y=180 | | -5x-68=4x+40 | | 123x+56=6 | | -6x-69=35+2x | | 2+y=0 | | 9x-19=6x+47 | | (b+9)(b-6)=0 | | -9x-40=3x+32 | | 6x-69=-3x+30 | | x^2+31x+43= | | Y=60+5x | | 3x^2-24x-60=0 | | 6-x+4=19 | | x^2+12x=-25 | | x^4+7x^3+8x^2-7x+15=0 | | 12c^2+19x-21=0 | | 12x^2+25-7=0 | | 10n=109 | | 12*-1=y | | (x+6)(x+6)-11=0 | | 12-20y=20 | | (y-1)(y-1)=16 | | 3(p-1)=4(2p+7) | | 5(5+x)=3(x+7) | | 8+5x+6(10x)=608+5x | | 2x=52 |